Production and perception of contrast: The case of the rise-fall contour in German - Kügler, Frank; Gollrad, Anja (Frontiers in Psychology, 2015)
This study investigates the phonetics of German nuclear rise-fall contours in relation to contexts that trigger either a contrastive or a non-contrastive interpretation in the answer. A rise-fall contour can be conceived of a tonal sequence of L-H-L. A production study elicited target sentences in contrastive and non-contrastive contexts. The majority of cases realized showed a nuclear rise-fall contour. The acoustic analysis of these contours revealed a significant effect of contrastiveness on the height / alignment of the accent peak as a function of focus context. On the other hand, the height / alignment of the low turning point at the beginning of the rise did not show an effect of contrastiveness. In a series of semantic congruency perception tests participants judged the congruency of congruent and incongruent context-stimulus pairs based on three different sets of stimuli: (i) original data, (ii) manipulation of accent peak, and (iii) manipulation of the leading low. Listeners distinguished nuclear rise-fall contours as a function of focus context (experiment 1 and 2), however not based on manipulations of the leading low (experiment 3). The results suggest that the alignment and scaling of the accentual peak are sufficient to license a contrastive interpretation of a nuclear rise-fall contour, leaving the rising part as a phonetic onglide, or as a low tone that does not interact with the contrastivity of the context.